汽车水泵轴连轴承与法兰合理过盈量设计 - 解芳; 刘明星; 冯长虹; 陈铁军 (Jixie chuandong)
Based on the loading and strength requirements of shaft-bearing and flange interference fit structure of an automobile water pump,the range of original magnitude of interference is determined by theoretical calculation,and the magnitude of interference is modified with considering the effect of temperature and rotational speed.In addition,the deformation,equivalent stress and contact pressure of the interference structure are analyzed by using the finite element method.The results show that the influence of the centrifugal force on the magnitude of interference can be neglected because the size and speed of the shaft-bearing and flange are both small.Moreover,because there is obvious stress concentration at the both ends of flange contact zone,so the maximum magnitude of interference should be modified by considering the effect on the structural strength.Finally,the reasonable magnitude of interference between shaft-bearing and flange is obtained as 0.0130.023mm.